Frequency of Hearing Defect and Ear Abnormalities in Newborns Conceived by Assisted Reproductive Techniques in Royan Institute - Seyed Ebrahim Ahmadi; Mohammad Reza Nateghi; Hamid Gourabi; Ramin Mozafari Kermani; Farnoush Jarollahi; Sodabeh Afsharpour; Jalil Kouhpayehzadeh; Abolhasan Shahzadeh Fazeli; Mahnaz Ashrafi (International Journal of Fertility and Sterility, 2010)
Background Assisted reproductive techniques (ART) are used with increasing frequency worldwide. The present research was conducted to determine the effects of ART on hearing defects and ear abnormalities.